2013
DOI: 10.1016/j.pbb.2013.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia-like disruptions of sensory gating by serotonin receptor stimulation in rats: Effect of MDMA, DOI and 8-OH-DPAT

Abstract: Schizophrenia pathophysiology is associated with alterations in several neurotransmitter systems, particularly dopamine, glutamate and serotonin (5-HT). Schizophrenia patients also have disruptions in sensory gating, a brain information filtering mechanism in response to repeated sensory stimuli. Dopamine and glutamate have been implicated in sensory gating; however, little is known about the contribution of serotonin. We therefore investigated the effects of several psychoactive compounds that alter serotoner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…A limitation of this study is that, while effects on S2:S1 ratio were highly consistent between the different cohorts and drug studies, there was variability in the amplitude of the individual P and N components of the waveforms, resulting in variability of drug effects on S1 vs. S2. It is unclear why there was this inconsistency although previous studies similarly found some variability of effects on waveform components when comparing MDMA with other serotonergic compounds [25] or following changes in experimental protocol [6,8,52]. Future studies should aim to replicate the present results in larger animal cohorts to reduce experimental variability and more clearly associate drug effects to individual waveform components.…”
Section: Interactive Effects Of D1 and D2 Receptors And Of 5-ht2a Andmentioning
confidence: 77%
See 4 more Smart Citations
“…A limitation of this study is that, while effects on S2:S1 ratio were highly consistent between the different cohorts and drug studies, there was variability in the amplitude of the individual P and N components of the waveforms, resulting in variability of drug effects on S1 vs. S2. It is unclear why there was this inconsistency although previous studies similarly found some variability of effects on waveform components when comparing MDMA with other serotonergic compounds [25] or following changes in experimental protocol [6,8,52]. Future studies should aim to replicate the present results in larger animal cohorts to reduce experimental variability and more clearly associate drug effects to individual waveform components.…”
Section: Interactive Effects Of D1 and D2 Receptors And Of 5-ht2a Andmentioning
confidence: 77%
“…A 2 mg/kg dose of MDMA ((±) 3,4 methylene-dioxymethamphetamine hydrochloride, Sigma Aldrich, St. Louis, MO, USA) was injected intraperitoneally. This was previously shown to elicit a paired-pulse sensory gating deficit [25]. Pretreatment drugs, haloperidol (Serenace®, Aspen Pharma Pty Ltd, St Leonards, NSW, Australia) 0.25 mg/kg, SCH23390 (Tocris Bioscience, Bristol, UK) 0.1 mg/kg, ketanserin tartrate (Tocris Bioscience, Bristol, UK) 2 mg/kg and WAY100635 maleate (Tocris Bioscience, Bristol, UK) 1 mg/kg, were all injected subcutaneously.…”
Section: Drugsmentioning
confidence: 85%
See 3 more Smart Citations